Penerapan BERT dalam Memetakan Opini Pengguna Instagram Terhadap Program Makan Bergizi Gratis - Rika Septiana Septiana; Ali Ibrahim; Endang Lestari; Yadi Utama (Universitas Budi Darma, 2026)
The Free Lunch Program is a new government initiative designed to improve students’ nutritional intake and enhance their focus during school activities. Its implementation has gained significant public attention, generating a variety of reactions across social media platforms, particularly Instagram. This study aims to examine public sentiment toward the program’s rollout in South Sumatra by collecting user comments from posts using the hashtag #mbgsumsel. The collected comments were processed through several stages, including data cleaning, text pre-processing, dataset partitioning, fine-tuning and model evaluation. The BERT model was employed due to its strong capability in capturing contextual meaning within text, making it more effective than conventional classification approaches. Experimental results indicate that the model achieved an akurasi of 88% in classifying sentiments. The test dataset consisted of 751 positive comments, 233 neutral comments, and 257 negative comments. Overall, this study provides a quantitative overview of how the public perceives the Free Lunch Program based on their social media expressions.